Research of evolution stages and schools of strategic management - Кононова, Олександра Євгеніївна (Technology audit and production reserves, 2016)
Analysis of literature is conducted and the content and nature of the main schools of strategic management are reviewed for: design school, planning school, positioning school, business school, cognitive school, training school, authority school, culture school, environment school and configuration school. Inconsistency of the authors concerning the characteristics systematization of strategy schools, as well as the emergence of new strategic management concepts require a reconsideration of existing classifications of strategic management methodology. The main problem in the absence of a well-established model of strategic management is not only an implementation of systematization for strategy schools, but considering each of them in terms of their contribution in the formation of modern strategic management paradigm. The study of the evolution of strategic management approaches identified the main 10 classic schools of strategic management. They are systematized in the table showing the main tools and disadvantages of each school. It may be noted that table allows to demonstrate the general situation of each school of strategic management in chronological order with the designation of authors.